Freestyle soccer tricks : tricks, flick-ups, catches - D'Arcy, Sean. (Buffalo, N.Y. : Firefly Books, 2008)
Provides step-by-step instructions and photographs for performing soccer tricks, such as the thinker, the switch, the shinny, and others.
5.0
5-8
Keywords: Soccer -- Juvenile literature; Soccer; Soccer